Correction: Defects-Rich Heterostructures Trigger Strong Polarization Coupling in Sulfides/Carbon Composites with Robust Electromagnetic Wave Absorption - Liu, Jiaolong; Zhang, Siyu; Qu, Dan; Zhou, Xuejiao; Yin, Moxuan; Wang, Chenxuan; Zhang, Xuelin; Li, Sichen; Zhang, Peijun; Zhou, Yuqi; Tao, Kai; Li, Mengyang; et al. (Nano-Micro Letters, 2024)
Defects-rich heterointerfaces integrated with adjustable crystalline phases and atom vacancies, as well as veiled dielectric-responsive character, are instrumental in electromagnetic dissipation. Conventional methods, however, constrain their delicate constructions. Herein, an innovative alternative is proposed: carrageenan-assistant cations-regulated (CACR) strategy, which induces a series of sulfides nanoparticles rooted in situ on the surface of carbon matrix. This unique configuration originates from strategic vacancy formation energy of sulfides and strong sulfides-carbon support interaction, benefiting the delicate construction of defects-rich heterostructures in MxSy/carbon composites (M-CAs). Impressively, these generated sulfur vacancies are firstly found to strengthen electron accumulation/consumption ability at heterointerfaces and, simultaneously, induct local asymmetry of electronic structure to evoke large dipole moment, ultimately leading to polarization coupling, i.e., defect-type interfacial polarization. Such “Janus effect” (Janus effect means versatility, as in the Greek two-headed Janus) of interfacial sulfur vacancies is intuitively confirmed by both theoretical and experimental investigations for the first time. Consequently, the sulfur vacancies-rich heterostructured Co/Ni-CAs displays broad absorption bandwidth of 6.76 GHz at only 1.8 mm, compared to sulfur vacancies-free CAs without any dielectric response. Harnessing defects-rich heterostructures, this one-pot CACR strategy may steer the design and development of advanced nanomaterials, boosting functionality across diverse application domains beyond electromagnetic response. Highlights: 1 A series of sulfides/carbon composites with sulfur vacancies-rich sulfides heterointerfaces are well-designed and developed via a simple one-pot carrageenan-assistant cations-regulated strategy. 2“Janus effect” of interfacial sulfur vacancies, which triggers strong defect-type interfacial polarization, are firstly intuitively confirmed by both theoretical and experimental investigations. 3 Optimized Co/Ni-carbon composites (CAs) imbued with sulfur vacancies-rich heterointerfaces displays broad absorption bandwidth of 6.76 GHz at only 1.8 mm, compared to sulfur vacancies-free CAs without any dielectric response.